Application of Coupled Electric Field Method for Eddy Current non-Destructive Inspection of Multilayer Structures, ISSN / e-ISSN 1058-9759 / 1477-2671 - Bouchala Tarek; Bachir Abdelhadi; Benoudjit Azeddine (Nondestructive Testing and Evaluation, 2015)
The development of fast and accurate method describing the electromagnetic phenomena intervening in eddy current non-destructive systems is very interesting, since it permits the design of reliable systems permitting the detection and the characterisation of defect in conductive materials. The coupled electric field method presented in this article can assume a large part of these objectives, because it is fast in comparison to the finite element method and easily invertible since the sensor impedance variation is an explicit function of target physical and geometrical characteristics. These advantages have motivated us to extend this method for multilayered structures, very interesting in aeronautic industry, by superposing the inductive effects in different layers. The impedance of an absolute sensor operating above three conducting layers will be calculated and compared to those obtained with finite element method. Afterwards, we shall exploit the model to study the effect of defect characteristics on the sensor impedance. Furthermore, regarding to the depth penetration effect, we shall make into evidence the necessity of accomplishing an optimal choice of the exciting field frequency during the inspection of multilayered materials. The essential importance of this method, besides of its rapidity, resides in its possibility to be extended to 2D irregular and 3D asymmetric configurations.